IMPROVING THE LEGAL FRAMEWORK FOR PROSECUTORIAL SUPERVISION OVER THE IMPLEMENTATION OF PUBLIC HEALTH LEGISLATION - Rajabov Daniyar Bakhtiyarovich (Journals Park Publishing, 2023)
The article discusses the need for prosecutorial control over the implementation of laws on health care, legal means of prosecutorial activity and their features, problems of national legislation and ways to solve them.
Keywords: prosecutor's office, prosecutor's supervision, medical legislation